The analytic attitude - Schafer, Roy (Karnac Books : Institute of Psycho-Analysis, 1993)
""The analytic attitude"" ranks as one of Freud's greatest creations. Both the findings of psychoanalysis as a method of investigation and its results as a method of treatment depend on its being consistent to a high degree. Yet Freud offered no concise, complex, generally acceptable formulation of what it is: his ideas, or a version of them, can only be derived from his papers on technique. Taking these ideas as a starting point, and with due regard to the contributions of other analysts over the years, Dr Schafer rises to the challenge of defining the ""ideal"" attitude that he come to aspir.